2011
DOI: 10.1029/2011jd016336
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl sulfide air-sea fluxes and biogenic sulfur as a source of new aerosols in the Arctic fall

Abstract: Dimethyl sulfide (DMS) and its oxidation products, which have been proposed to provide a climate feedback mechanism by affecting aerosol and cloud radiative properties, were measured on board the Canadian Coast Guard ship Amundsen in sampling campaigns in the Arctic in the fall of 2007 and 2008. DMS flux was calculated based on the surface water measurements and yielded 0.1–2.6 μmol m−2 d−1 along the Northwest Passage in 2007 and 0.2–1.3 μmol m−2 d−1 along Baffin Bay in 2008. DMS oxidation products, sulfur dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 60 publications
(118 reference statements)
4
65
2
1
Order By: Relevance
“…Although wind is considered an important factor in the seaair exchange of sea salt, correlations in this study between wind speed and sea salt sulfate concentrations for coarse-and fine-mode aerosols were not significant (R 2 ∼ = 0.1), which is consistent with previous studies (Lewis and Schwartz, 2004;Rempillo et al, 2011;Seguin et al, 2011;Jaeglé et al, 2011).…”
Section: Sea Salt Sulfatesupporting
confidence: 81%
See 3 more Smart Citations
“…Although wind is considered an important factor in the seaair exchange of sea salt, correlations in this study between wind speed and sea salt sulfate concentrations for coarse-and fine-mode aerosols were not significant (R 2 ∼ = 0.1), which is consistent with previous studies (Lewis and Schwartz, 2004;Rempillo et al, 2011;Seguin et al, 2011;Jaeglé et al, 2011).…”
Section: Sea Salt Sulfatesupporting
confidence: 81%
“…Results show approximately uniform non-sea-salt sulfate concentrations for samples in the Labrador Sea and further north (130 ± 21 ng m −3 ). Sulfate concentrations, especially nonsea-salt sulfate, in this research were found to be higher than previous Arctic studies above the ocean during fall (2007)(2008) (Rempillo et al, 2011) and at higher latitudes at Alert in summer (1993)(1994) (Norman et al, 1999) and about the same as at Barrow, Alaska during July (1997-2008) (Quinn et al, 2009). One reason could be higher biological activity and biogenic aerosols from phytoplankton during summer, as addressed in the next section.…”
Section: Non-sea-salt Sulfatecontrasting
confidence: 50%
See 2 more Smart Citations
“…109 U prirodi nastaje iz antropogenih, geogenih, biogenih i fotokemijskih izvora. [108][109][110] Glavni antropogeni izvori su proizvodnja energije, industrija, termoelektrane, promet, spaljivanje otpada. Geogeni izvori uključuju vulkane i termalne izvore, dok biogeni obuhvaćaju hlapljive organske spojeve bogate sumporom koji odlaze u atmosferu gdje se iz njih proizvodi SO 2 .…”
Section: Anion S 4 Ounclassified